ANALISIS STRATEGI BERMAIN DALAM MENINGKATKAN SOSIAL EMOSIONAL ANAK PADA KEGIATAN MOVING CLASS DILABORATORIUM PAUD BBPMP JAWA BARAT - Kurnia, Vina; Suprapmanto, Joko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of play strategies in moving class activities and their impact on the social-emotional development of early childhood children at the Early Childhood Education Laboratory (PAUD) BBPMP West Java. The research method used is descriptive qualitative with techniques including observation, interviews, and documentation. The results show that play strategies in moving class provide children with the opportunity to choose activities according to their interests, thereby encouraging independence and social interaction. This strategy has a positive impact on children's social-emotional development, such as increased self-confidence, courage to interact, and the ability to manage emotions. These findings are in line with Piaget's theory which emphasizes the importance of exploration, and Vygotsky's theory which highlights the role of social interaction. In conclusion, play strategies in moving class are effective in enhancing the social and emotional development of early childhood children.